PENINGKATAN PEMBELAJARAN MATEMATIKA POKOK BAHASAN RELASI DAN FUNGSI PADA SISWA KELAS X KL SMK NEGERI 1 SITUBONDO DENGAN MENGGUNAKAN METODE STAD - Sidawi, S (Kadikma, 2019)
This type of research is classroom action research. The subjects of this research were 38 students of Class X KL SMK Negeri 1 Situbondo, Situbondo Regency. The purpose of this research is to describe the process of learning mathematics using the STAD method on the subject of Relations and Functions. Data collection tools and methods used in this research were tests, observations, and questionnaires. The results of this study 80% of students are happy about cooperative skills, and 75.5% argue that the device used is new. In addition, students' responses about process skills 82.6% were happy and 72.2% thought that the process skills used were relatively new. From these data shows that students like to be involved in learning using cooperative skills and process skills, especially in the process of observing skills where the opinions of students feel happy in doing observations by 95.7%. Keyword: STAD, student achievement, cooperative skills, process skills, relations and functions